EVALUATING THE IMPACT OF CONTINUING EDUCATION ON JOB SATISFACTION AND PERFORMANCE AMONG LABORATORY TECHNICIANS IN SAUDI ARABIA: A MIXED-METHODS STUDY - Ali Taleb Aldhafeeri, Faisal Taleb Aldhafeeri, Masad Farhan Aldhafeeri, Fahad Atiah Alanazi, Bader Zuwayni Aldhafeeri, Maryam Fayadh Alanazi, (Chelonian Research Foundation, 2022)
Continuing education plays a crucial role in the professional development of laboratory technicians, ensuring they remain up-to-date with the latest advancements in their field. This mixed-methods study aims to evaluate the impact of continuing education on job satisfaction and performance among laboratory technicians in Saudi Arabia. A total of 150 laboratory technicians from various healthcare facilities in Saudi Arabia participated in the study. Quantitative data were collected using a survey questionnaire, while qualitative data were gathered through semi-structured interviews with a subset of 20 participants. The survey assessed job satisfaction using the Job Satisfaction Survey (JSS) and self-reported performance using a 5-point Likert scale. Interview data were analyzed using thematic analysis. The results showed that participants who regularly engaged in continuing education reported higher levels of job satisfaction (M = 4.2, SD = 0.6) compared to those who did not (M = 3.5, SD = 0.8), t(148) = 5.78, p < .001. Moreover, participants who engaged in continuing education reported better performance (M = 4.4, SD = 0.5) than those who did not (M = 3.8, SD = 0.7), t(148) = 6.12, p < .001. The qualitative findings revealed that continuing education helped technicians feel more confident in their skills, enhanced their problem-solving abilities, and improved their communication with colleagues and patients. The study highlights the importance of continuing education in promoting job satisfaction and performance among laboratory technicians in Saudi Arabia and provides insights for healthcare organizations to support their professional development. Keywords: continuing education, job satisfaction, performance, laboratory technicians, mixed-methods, Saudi Arabia